Examination of physical, motor and physiological features of athletes and wrestlers in the age group of 12-14 years old in terms of branching - Bulgay, C.; Çetin, E. (International Journal of Applied Exercise Physiology, 2018)
The purpose of the study is to compare the physical, motor and physiological features of students in the age group of 12-14 years old who regularly practice in athletics and wrestling sports with non-sports students, and explore its impacts on the sports students' level of branching. The research group was selected among Keçiören Mecidiye Secondary School and Alaeddin Ozdenören Imam Hatip Secondary School students in Ankara. The research group consisted of 47 students; 15 students in the age group of 12-14 years old who are engaged in regular athletics training, 17 students in the same age group who are engaged in regular wrestling training and 15 volunteers in the same age group who do not do sports. Measurements included age, height, body weight, Agility (T-test), hand grip strength, standing jump, vertical jump, body fat percentage, flamingo balance, flexibility, 1 min shuttle, BMI, 30 m speed run, 1000 m run-walk tests. The analysis of the data was evaluated according to the results of the Levene test for homogeneity. If the result was homogeneous, ANOVA method, otherwise Kruskal Wallis comparison test was used. In variables whose averages differed as result of multiple comparisons, the TUKEY test was used to find which groups these differences stemmed from. The results of agility, right and left hand grip strength, flexibility, 1 min shuttle, Body Mass Index (BMI), 30 m speed, 1000 m run-walk tests were statistically significant. However, the results for height, weight, age, long jump, flamingo balance, body fat percentage, vertical jump tests were not statistically significant. When we look at the results, it is found that the best results for 1000 m run-walk, 30 m speed run, agility (T-test), height, long jump, vertical jump were recorded in the athletics group. It has been observed that the wrestler group has better results in body weight, body fat percentage, grasp strength, flamingo balance, 1 minute shuttle and flexibility parameters. The values of the control group were found to be lower than those who were engaged in athletics and wrestling as they did not exercise regularly. When the differences between the groups are evaluated, it can be said that there is a tendency towards branching in a branch in the age group of 12-14 years old.